The most beautiful bibles - Fingernagel, Andreas; Gastgeber, Christian (Hong Kong ; Los Angeles Taschen, 2008)
Covers examples from various epochs of the Middle Ages, presenting the Bible as it was visualized in both theological and historical contexts. This title describes each manuscript in detail and explores the evolution of the Bible as well as the medieval understanding of history that is inherent in these versions of the Bible.
Bible production in medieval monasteries -- From royal collection to National Library -- Textual traditions and editorial revisions : Bibles from their beginnings to the standardized Bibles of the 13th century -- Magnificence and grandeur : luxury Bible manuscripts -- Biblical exegesis from the Church Fathers to scholasticism -- Medieval versions of history in world chronicles and history Bibles -- The juxtaposition of the Old and New Testaments in typological picture Bibles -- Bible manuscripts of the Jewish and Eastern Orthodox faiths.
At head of title: Österreichische Nationalbibliothek.
Keywords: Bible -- Illustrations -- History; Illumination of books and manuscripts -- History